Temporal and Spatial Distribution Changes, Driving Force Analysis and Simulation Prediction of Ecological Vulnerability in Liaoning Province, China - Dong Li; Chongyang Huan; Jun Yang; Hanlong Gu (Land, 2022)
As China’s main grain-producing region, the ecological security pattern of Liaoning Province has an extremely important impact on the ecological security of Northeast China and even the whole country. Furthermore, the construction of the ecological security pattern is restricted by the ecological vulnerability assessment in order to explore the ecological vulnerability pattern of spatial distribution and the trend of future vulnerability development in Liaoning Province and guide how to formulate ecological protection policies scientifically. Based on the sensitivity–resilience–pressure (SRP) conceptual model which is combined with natural and socio-economic factors, the ecological vulnerability evaluation index system of Liaoning Province is established in this paper. This paper also evaluates the ecological vulnerability of Liaoning Province from 2010 to 2020 and analyzes the driving factors by using a geographic detector and the CA-Markov model. Moreover, the study forecasts the growing tendency of vulnerability in 2025. The results show that (1) the ecological vulnerability of Liaoning Province is mainly light and has medium vulnerability, which gradually decreases from northwest to southeast; (2) the spatial heterogeneity of the ecological vulnerability index (EVI) is very significant in the southeast and northwest region but not significant in the middle; (3) from the past decade to the next five years, the ecological vulnerability of Liaoning Province has been improving, and the overall distribution pattern of ecological vulnerability is relatively stable; (4) the analysis of driving factors indicates that the impact of natural environmental factors such as land-use type and habitat quality on EVI is more significant than socio-economic factors such as population density. The research results implicate that it is necessary to formulate an ecological protection and restoration plan in Liaoning Province to prevent further ecological degradation in high-value areas of northwest Liaoning, and to balance the relationship between human development and ecological protection and restoration in the metropolitan district.